2008
DOI: 10.1097/tp.0b013e318170b4cd
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Coronary Endothelial Dysfunction on Adverse Long-Term Outcome After Heart Transplantation

Abstract: This is the first study showing that epicardial endothelial dysfunction independently predicts outcome in HTx patients providing functional and prognostic information that complete angiographic risk factor assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…[13][14][15] Nevertheless, there is a considerable heterogeneity in the magnitude of vascular dysfunction in individuals with similar risk factor profile. 16,17 In this regard, vascular dysfunction may be seen as an important ''integrative factor'' of the inherent atherosclerotic risk in an individual, taking into account the cumulative risk of various coronary risk factors, unknown variables, and the genetic susceptibility of vascular endothelium toward coronary risk factors.…”
Section: Vascular Function and Myocardial Perfusionmentioning
confidence: 99%
“…[13][14][15] Nevertheless, there is a considerable heterogeneity in the magnitude of vascular dysfunction in individuals with similar risk factor profile. 16,17 In this regard, vascular dysfunction may be seen as an important ''integrative factor'' of the inherent atherosclerotic risk in an individual, taking into account the cumulative risk of various coronary risk factors, unknown variables, and the genetic susceptibility of vascular endothelium toward coronary risk factors.…”
Section: Vascular Function and Myocardial Perfusionmentioning
confidence: 99%
“…However, published data are not consistent between studies. Kübrich et al [62] , in a larger cohort, found no correlation between epicardial and microvascular disease and found that, whilst microvascular dysfunction demonstrated by CFR was a predictor of outcome (death or adverse cardiovascular event) in the univariate analysis, it did not predict outcome in the multivariate analysis.…”
Section: Echocardiographymentioning
confidence: 94%
“…This effect could ultimately increase local cardiac inflammation and consequently facilitate the development of CAV. Although the function and effect of CNI-induced endothelial dysfunction in the pathogenesis of CAV is poorly understood, it has been demonstrated that both CsA and TAC induce vascular oxidative stress, increased endothelin-1 (ET-1) release, and contribute to the dysregulation of endothelial nitric oxide synthase (NOS) in the kidney [44,[62][63][64] . Indeed CNI-induced endothelial dysfunction includes the attenuation of the endothelium to release NO [65] , a physiologically relevant mechanism because decreased NO bioavailability is related to the production of reactive oxygen species (ROS) and thus oxidative stress [65] .…”
Section: Impact Of Immunosuppressive Regimens On Cavmentioning
confidence: 99%